Characterization of a lytic Pseudomonas aeruginosa phage vB_PaeP_ASP23 and functional analysis of its lysin LysASP and holin HolASP - Cui, Jiaqi; Shi, Xiaojie; Wang, Xinwei; Sun, Huzhi; Yan, Yanxin; Zhao, Feiyang; Zhang, Can; Liu, Wenhua; Zou, Ling; Han, Lei; Pan, Qiang; Ren, Huiying (Frontiers in Microbiology, 2023)
In this study, we isolated a novel lytic P. aeruginosa phage (vB_PaeP_ASP23) from sewage of a mink farm, characterized its complete genome and analyzed the function of its putative lysin and holin. Morphological characterization and genome annotation showed that phage ASP23 belonged to the Podoviridae family genus phikmvvirus, and it had a latent period of 10 min and a burst size of 140 pfu/infected cell. In minks challenged with P. aeruginosa, phage ASP23 significantly reduced bacterial counts in the liver, lung, and blood. The whole-genome sequencing showed that its genome was a 42,735-bp linear and double-stranded DNA (dsDNA), with a G+C content of 62.15%. Its genome contained 54 predicted open reading frames (ORFs), 25 of which had known functions. The lysin of phage ASP (LysASP), in combination with EDTA, showed high lytic activity against P. aeruginosa L64. The holin of phage ASP23 (HolASP) was expressed by M13 phage display technology. Though HolASP exhibited a narrow lytic spectrum, it was effective against Staphylococcus aureus and Bacillus subtilis. However, these two bacteria were insensitive to LysASP. The findings highlight the potential of phage ASP23 to be used in the development of new antibacterial agents.